Assessment of the economic potential: COx-free hydrogen production from renewables via ammonia decomposition for small-sized H2 refueling stations. (October 2019) - Lee, Boreum; Park, Junhyung; Lee, Hyunjun; Byun, Manhee; Yoon, Chang Won; Lim, Hankwon
Abstract: In this paper, techno-economic feasibility assessment on ammonia decomposition as a CO x -free H2 production method for a small-scale on-site H2 refueling station with a capacity of 30 m 3  h −1 in Korea was conducted to evaluate the feasibility of the proposed process in terms of technical and economic aspects. A robust process simulation model validated by experimental data from a laboratory-scale reactor was developed. Based on the process simulation model, economic feasibility studies were performed in terms of itemized cost estimation, profitability analysis, and sensitivity analysis. The itemized cost estimations showed a reduced unit H2 production cost of 6.27 $ kgH2 −1 for 30 m 3  h −1 compared to 9.97 $ kgH2 −1 for 0.9 m 3  h −1 (laboratory). The unit H2 selling price considering both production and dispensing was 9.06 $ kgH2 −1, comparable to the current equivalent gasoline cost of 10.65 $ kgH2 −1 . Different depreciation methods produced slight differences in the net present value, discounted payback period, and present value ratio. For a new depreciation method, the net present value was $318, 666, the discounted payback period was 2.24 years, and the present value ratio was 3.35, which confirmed the economic feasibility of this technology. Sensitivity analysis showed that the most important economic factor for the unit H2 production cost was the raw material (ammonia); in addition, the H2 selling price considerably affected the net present value, which critically influenced the profitability of the proposed project. Graphical abstract: Image 1 Highlights: Techno-economic feasibility assessment on ammonia decomposition was carried out. Process simulation model reflecting experimental data was developed. A unit H2 production cost of 6.27 $ kgH2 −1 was obtained for 30 m 3  h −1 . H2 selling price as the most influential economic factor was identified.